Making and Evaluating Visible Light Splitters Using Polyethylene Kitchen Wrap - Kurihara, Atsutoshi; Osada, Yuto; Bao, Yue (Transactions on Engineering and Computing Sciences, 2024)
We propose a method of creating an inexpensive visible light range wave plate using a birefringent material—kitchen wrap—and an evaluation method using a camera and projector. By stacking the appropriate number of kitchen wraps, any wave plate corresponding to any color can be created. The light of the projector is photographed using a camera through a kitchen wrap sandwiched between polarizing plates arranged in the crossed-Nicols condition. First, by rotating the kitchen wrap, the optical axis was obtained based on the change in luminance. Next, by increasing the number of kitchen wraps, the wavelength deviation per sheet was measured based on the change in luminance. The experimental results confirmed that polyethylene wrap is suitable as the material of the wave plate, and the optical axis is tilted by 45° with respect to the cut surface.